Analysis Performance French Fries Business Income Studies Case at UD. Potatoes House, Kabupaten Pasuruan - Teguh Sarwo Aji; Wardatun Nafisah (CV. Satria Jaya, 2026)
This study aims to analyze the income level of the French fries business at U D. Potatoes House, Pasuruan Regency, and to evaluate the company's ability to generate net profit from its sales activities. The study was conducted from May to June 2026. The determination of the research location and respondents was done intentionally (purposive sampling). The data used consisted of primary and secondary data obtained through observation, interviews, and documentation from related agencies. Data analysis was carried out using revenue, cost, income, and profitability analysis. The results of the study showed that in May UD. Potatoes House me ncatat obtained total revenue of Rp20,190,000, with total production costs of Rp11,929,075, resulting in revenue of Rp. 8,260,925. Meanwhile, in June 202 6 total revenue decreased to Rp17,430,000, with total production costs of Rp. 10,309,019, resulting in a revenue of Rp7,120,981. The level of profitability measured using the Return on Investment (ROI) indicator also decreased during the study period. The Earning After Tax (EAT) value was recorded at Rp8,327,512 in May and decreased to Rp7,193,268 in June. This decrease caused the ROI value to decrease from 72.51% to 62.63%. These results indicate that every investment of Rp100 is able to generate a net profit of between Rp72.51 and Rp. 62.63. Despite the decline in profitability due to fluctuations in revenue and income, UD. Potatoes House is still able to generate profits so it is worth continuing to run and develop.